Short Communication: Isolation and screening of polyhydroxylalkanoates producing microorganisms from Thailand: PHA Producing Microorganisms (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pungsungvorn N, Wisetsing A. 2021. Short Communication: Isolation and screening of polyhydroxylalkanoates producing microorganisms from Thailand. Biodiversitas 22: 4963-4967. Polyhydroxylalkanotes (PHAs) are polyesters produced in nature by numerous microorganisms. They are biodegradable and are used in the production of bioplastics. In this study, one hundred twenty samples from different regions of Thailand were collected and screened for polyhydroxylalkanoates (PHAs) producing microorganisms. The samples were screened on YM agar containing 0.5 µg Nile-red/mL (YM-NR). Only one isolate of yeast (Y1) gave a positive result on PHA accumulation. The yeast isolate (Y1) was identified as Candida tropicalis by API 20C AUX kit and 18S rRNA nucleotide comparison. The yeast isolate Y1 produced 2.62% PHA   when grown in synthetic N-limiting medium using rice straw hydrolysate as carbon source. The selected four bacteria (B1, B2, B3 and B4) were identified by BlastN of 16S rRNA as Enterobacter cloacae, Enterobacter carcerogenus, Escherichia coli and Klebsiella pneumonia, respectively. The selected yeast and bacterial strains gave PHA content of 2.62, 2.76, 5.38, 3.66 and 0.44%, respectively, in synthetic N-limiting medium using rice straw hydrolysate. Hence, these microorganisms could be used in PHA production from biomass in the future.
Keywords: biodiversity; bioplastic; PHA; polyester; rice straw